INCREASING THE KNOWLEDGE OF MOTHERS AND FAMILIES ABOUT THE PROBLEMS THAT OFTEN ARISE IN NEWBORNS THROUGH THE PROGRAM KIPRAH INDONESIA RRI MALANG - Dwi Yuliawati; Innas Tiara Ardhiani (Universitas Airlangga, 2023)
Newborns are prone to health problems due to a weak body defense system. Some problems that commonly arise in neonates include diseases in the mild category (which are common), for example: jaundice (physiological jaundice), vomiting, seborrheic dermatitis, oral trush, diarrhea, fever, diapper rush (diaper rash), miliariasis, constipation, and others. One of the preventive efforts to prevent complications in newborns is by providing health education aimed at increasing public knowledge about problems that often arise in newborns so that they can identify and take appropriate anticipatory and handling steps from existing problems. Community service activities are carried out through talk show activities in the form of questions and answers between radio broadcasters and speakers regarding the theme of activities that have been previously determined and broadcast live streaming on the Youtube channel of RRI Malang in the Kiprah Indonesia program. The activity was carried out on September 5, 2022 with a duration of time during live Youtube, which is about 60 minutes. Community participation from the talk show is indicated by the total viewers on the You tube page of RRI Malang, which is 69 times watched and 10 “like”. Providing education in this community service activity is expected to affect the behavior of mothers and families in the detection and treatment of problems that often arise in newborns.